Kepuasan Followers Atas Pemberitaan RUU TNI di Instagram @narasinewsroom Periode 13-20 Maret 2025 - Shilvia Yulianti Sumarna; Henny Sri Mulyani; Maimon Herawati (Penerbit Jurnal Indonesia, 2026)
The growth of social media has positioned Instagram as one of the primary sources of information for Indonesian society (Habibah & Irwansyah, 2021). This study aims to examine the level of satisfaction among followers of @narasinewsroom regarding coverage of the Revision of the Indonesian National Armed Forces Law (RUU TNI) during March 13–20, 2025. Employing the Uses and Gratifications theory through Palmgreen's Gratifications Sought (GS) and Gratifications Obtained (GO) model, this study used a descriptive quantitative approach with a survey questionnaire distributed to 100 active followers who had accessed RUU TNI-related content. Data were analyzed using the Wilcoxon Signed Ranks Test and mean score comparison. The findings reveal a significant difference between GS and GO (sig. 2-tailed = 0.001 ≤ 0.1), with a total mean GS of 426.6 exceeding the GO mean of 418.0. This indicates that followers have not yet reached satisfaction across the four dimensions examined: information, personal identity, social integration and interaction, and entertainment. The largest gap was found in the entertainment dimension, while the smallest appeared in social integration and interaction. These findings suggest that although information needs were relatively met, limitations in content format and the complexity of the issue affected overall audience satisfaction. Audiences expect more varied, interactive, and accessible content, particularly when covering politically sensitive policy issues such as the RUU TNI. These results underscore the importance of innovation in digital news content presentation to more optimally meet audience expectations.